Scattering upon a mixed dielectric-conductor body: A time-domain approach. - Gibson, Dan Vladimir. (University of Ottawa (Canada), 1992)
A time-domain integral equation technique is presented for calculating the behaviour of a mixed dielectric - conductive body subjected to a transient plane wave. The incident pulse is a smooth Gaussian pulse, approximating a delta function. We develop an original formulation capable of calculating the electric and magnetic fields on or outside the surface of the scatterer from the moment the incident wave hits the target. The result of the calculations is an impulse response providing information, via the Fourier transform, on the distribution of fields over a broad range of frequencies.
Keywords: Engineering, Electronics and Electrical.